Evaluación de parámetros productivos en razas mestizas de engorde con implante (zeranol) en Belisario Quevedo - Herrera Montes, Cristian Gabriel (2021)
This research was conducted in the parish of Belisario Quevedo at an altitude of 2803 meters above sea level, where we found a humid mountainous climate, located in the southwest of Latacunga Canton. The research was carried out with 20 animals, which were divided into two groups (A and B), each group consisted of 10 cattle, two animals of Brown swiss, Holstein friesian, Red Holstein, Angus and Normande breeds, between 6 and 7 months of age with an average weight between 170 and 396 kg, completely healthy and dewormed one month before the research, with a natural grass diet. Zeranol was administered as a subcutaneous implant in the base of the ear at a dose of 36 mg in group A and group B were control animals. Within the analysis, in productive parameters we can establish in the weight gain according to the p-value of 0.0001 there is a statistical difference where the animals with zeranol have a higher weight gain of 1.23kg and the animals without zeranol of 0.83kg. In consumption we can observe that there is no statistical difference since the p-value is 0.69 and in conversion we can observe that there is a statistical difference since the p-value is 0.0038, where the animals with zeranol have a conversion of 3.76kg and the animals without zeranol have a conversion of 6.04kg. Analyzing the testicular length and contour, the animals using anabolics we can observe that the length is 16.87cm while the animals not using anabolics have a length of 16.57cm and in contour the animals not using zeranol measure 32.95 cm and the animals using zeranol 32.07cm. When analyzing the cost per kilogram of weight gain for the breeds versus anabolics, we can see that the animals that used zeranol produced a kilogram of weight gain at $1.13 and the animals that did not use zeranol produced a kilogram of weight gain at $1.27.